Adaptation of American College of Rheumatology Rheumatoid Arthritis Disease Activity and Functional Status Measures for Telehealth Visits. Issue 12 (10th December 2021) - England, Bryant R.; Barber, Claire E. H.; Bergman, Martin; Ranganath, Veena K.; Suter, Lisa G.; Michaud, Kaleb
Abstract : Objective: To provide guidance on the implementation of recommended American College of Rheumatology (ACR) rheumatoid arthritis (RA) disease activity and functional status assessment measures in telehealth settings. Methods: An expert panel was assembled from the recently convened ACR RA disease activity and functional status measures working groups to summarize strategies for implementation of ACR‐recommended RA disease activity (the Clinical Disease Activity Index [CDAI], Disease Activity Score in 28 joints using the erythrocyte sedimentation rate or the C‐reactive protein level [DAS28‐ESR/CRP], Patient Activity Scale II [PAS‐II], Simplified Disease Activity Index [SDAI], and Routine Assessment of Patient Index Data 3 [RAPID3]) and functional status (the Health Assessment Questionnaire II [HAQ‐II], Multidimensional Health Assessment Questionnaire [MDHAQ], and PROMIS physical function 10‐item short form [PROMIS PF‐10]) measures in telehealth settings. Results: Measures composed of patient‐reported items (disease activity: PAS‐II, RAPID3; functional status: HAQ‐II, MDHAQ, PROMIS PF‐10) require minimal modification for use in telehealth settings. Measures requiring formal joint counts (the CDAI, DAS28‐ESR/CRP, and SDAI) can be calculated using patient‐reported swollen and tender joint counts. When the feasibility of laboratory testing is limited, the CDAI can be used in place of the SDAI, and scoring modifications of the DAS28‐ESR/CRP without the acute‐phase reactant are available. Assessment of the validity of these modifications is limited. Implementation of these measures can be facilitated by electronic health record collection, mobile applications, and provider/staff administration during telehealth visits. Conclusion: The ACR‐recommended RA disease activity and functional status measures can be adapted for use in telehealth settings to support high‐quality clinical care. Research is needed to better understand how telehealth settings may impact the validity of these measures.